High-strength and high-conductivity copper alloy wire and preparation method thereof
By adding an appropriate amount of Sn element to the copper alloy wire and controlling the microstructure structure, the problem of brittle fracture of existing copper alloy wires under alternating stress is solved, and the comprehensive effect of high strength, excellent conductivity and good tensile fatigue performance is achieved.
Patent Information
- Application Number
- CN202411660121.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-28
AI Technical Summary
Existing copper alloy wires are prone to brittle fracture under the action of alternating stress, which is difficult to meet the requirements of high strength, high conductivity and excellent tensile fatigue properties.
By adding 0.10 to 1.0 wt% of Sn elements to the copper matrix, a solid solution structure is formed, and the area percentage of the <100>, <110> and <111> silk textures in the microstructure of the cross-section are controlled to improve the tensile strength and electrical conductivity of the wire.
The high strength, excellent conductivity and good tensile fatigue properties of copper alloy wires are achieved, the tensile strength is above 400MPa, the conductivity is above 65% IACS, and the number of cycles reaches more than 10,000 times.
Smart Images

Figure BDA0005143081790000061 
Figure BDA0005143081790000071
Abstract
Description
Technical Field
[0001] The invention belongs to the field of copper alloys, and in particular relates to a high-strength and high-conductivity copper alloy wire and a preparation method thereof. Background Art
[0002] Copper alloys, as typical electronic materials, are an important material basis for the development of modern electronic industry and science and technology, especially high-performance copper alloys, which are key basic materials in high-tech fields such as automobiles, microelectronics, and aerospace, and also play an important supporting role in the development of electronic information technology.
[0003] Taking the automobile industry as an example, automobile wiring harnesses, as an important component of the whole vehicle, account for a large proportion of the total weight of the whole vehicle. There are two main lightweight ideas for the wires, which are the main components of the wiring harnesses. One is to replace copper wires with lighter aluminum wires. However, due to the insufficient performance of aluminum wires, they cannot meet the use requirements in many high-performance situations; the other is to reduce the wire diameter to achieve the purpose of lightweighting. How to reduce the wire diameter so that the small wire diameter wire harness can meet the requirements of signal transmission, the tensile strength of crimping, the bonding force of terminal insertion, etc. is the key issue of copper alloy wires under the trend of lightweighting. In order to meet the requirements of mechanical properties, alloyed copper wires such as Cu-Sn, Cu-Ag, Cu-Mg and copper-clad steel solutions have emerged. In particular, Cu-Sn wires are favored by the majority of new energy automobile companies because of their superior strength and conductivity.
[0004] The metal conductor used in wiring harnesses, copper alloy wires, are prone to sudden brittle fractures after long-term cyclic application of stress, although the stress-strain value does not exceed the limit of the material itself. These strain loads include tensile loads, bending loads, and thermal loads that may exist in harsh environments. To address the above problems, it is necessary to develop a copper alloy wire that meets the requirements of high strength and high conductivity, as well as excellent tensile fatigue performance. Summary of the invention
[0005] The first technical problem to be solved by the present invention is to provide a high-strength and high-conductivity copper alloy wire with excellent tensile fatigue performance in view of the deficiencies in the prior art.
[0006] The technical solution adopted by the present invention to solve the first technical problem is: a high-strength and high-conductivity copper alloy wire, the mass percentage composition of the copper alloy wire is Sn: 0.10-1.0%, and the balance is Cu and inevitable impurities; in the microstructure of the cross section of the copper alloy wire, <100> , <110> and <111> Area percentage of silk texture S 100 , S 110 and S 111 Satisfaction: S 100 / (S 110 +S111 )≥0.8.
[0007] Sn is the main strengthening element in the alloy wire of the present invention. With the increase of Sn content, the hardness and strength of the wire gradually increase. When a small amount of Sn alloy element is added to the copper matrix, Sn mainly exists in the copper matrix in the form of solid solution. On the one hand, Sn solute atoms dissolve into the copper matrix, making the lattice constant of the copper matrix larger and causing lattice distortion, which has an obstructive effect on dislocations moving on the slip plane; on the other hand, Sn atoms segregated on the dislocation line play a pinning role on the dislocation, and Sn above 0.10wt% can play a considerable strengthening effect. With the increase of Sn element content in the matrix, the lattice constant and lattice distortion of the copper matrix increase, the strengthening effect becomes greater, and the hardness and strength increase accordingly. At the same time, with the increase of Sn element content, the conductivity of the alloy decreases significantly. This is because the conduction of metals is the result of the directional movement of free electrons, while the resistance is mainly caused by the scattering effect of solid solution atoms, impurities, dislocations, vacancies and interfaces in the matrix on electrons. The presence of Sn solute atoms causes lattice distortion, which intensifies the scattering of electrons and increases the resistivity of the alloy. As the Sn content increases, the resistivity of the alloy will gradually increase and the conductivity will significantly decrease. From the perspective of controlling the comprehensive performance of the alloy wire, the amount of Sn element added should not be too much, preferably less than 1.0wt%, so the Sn content of the present invention is 0.10-1.0wt%.
[0008] In the microstructure of the cross section of the copper alloy wire of the present invention, <100> , <110> and <111> Area percentage of silk texture S 100 , S 110 and S 111 Satisfaction: S 100 / (S 110 +S 111 )≥0.8.
[0009] During plastic processing and heat treatment, copper alloy wire will undergo a series of changes in crystal orientation, that is, a change in texture state. The properties of copper alloys with the same alloy composition will also change under different texture states. The texture type in the microstructure of the copper alloy wire of the present invention is mainly <100> , <110> and <111> The inventor has repeatedly studied and tested various texture states of copper alloy wires and found that when the microstructure of the cross section of the copper alloy wire is <100> , <110> and <111> Area percentage of silk texture S 100 , S 110 and S 111 Satisfaction: S 100 / (S 110 +S 111)≥0.8, the copper alloy wire has good tensile strength and conductor performance, and the tensile fatigue performance is also very good.
[0010] Preferably, in the microstructure of the cross section of the copper alloy wire of the present invention, the surface layer and the center layer are <110> Area percentage of silk texture S 表110 and S 中110 Satisfaction: S 表110 / S 中110 ≥1.2, the central layer is a region that is proportionally reduced with the central point of the cross section of the copper alloy wire as the center, and the area of the central layer on the cross section of the copper alloy wire accounts for 36%, and the surface layer is the region on the cross section of the copper alloy wire excluding the central layer.
[0011] When the copper alloy wire is further stretched, especially in the stretching process for the purpose of reducing the diameter, there is a difference in the stress and strain conditions on the surface and center of the wire. The inventors have repeatedly studied and tested the texture state of the copper alloy wire with different gradients from the surface to the center and found that in the microstructure of the cross section of the copper alloy wire, the surface layer and the center layer are different. <110> Area percentage of silk texture S 表110 and S 中110 Satisfaction: S 表110 / S 中110 When ≥1.2, the copper alloy wire has more ideal tensile fatigue performance and is more resistant to further diameter reducing and stretching processing.
[0012] Preferably, the average grain size in the microstructure of the cross section of the copper alloy wire of the present invention is 0.5 to 10 μm. Controlling the crystallization of the copper alloy wire can better balance the comprehensive performance of the wire. If the average grain size is too small, the grains are too fine, the work hardening effect is poor, and the tensile strength is difficult to meet the requirements; on the contrary, if the average grain size is too large, the grains are too coarse, uneven deformation is prone to occur, resulting in poor tensile fatigue performance.
[0013] Preferably, the mass percentage composition of the copper alloy wire of the present invention also includes at least one element selected from Zn, Mg, Al, Ni, Mn, Si, Ti, Cr, Ag, Zr, In, P and B with a total amount of 0.001-0.5%. The appropriate addition of the above optional elements helps to refine the grains, deoxidize and remove carbon, improve the purity of the alloy, and thus improve the electrical conductivity of the alloy. Some elements can also form precipitation strengthening phases through deformation heat treatment processes, promote the precipitation of alloy elements, enhance the alloy strengthening effect, and make the alloy have higher strength and hardness. When the total amount of the above optional elements is greater than or equal to 0.001wt%, the above strengthening effect can be achieved, but if the total amount of the above optional elements exceeds 0.5wt%, the solubility limit of the Sn element will be reduced or the degree of solid solution in the matrix will be increased, significantly reducing the electrical conductivity and tensile fatigue performance. Therefore, the present invention controls the total amount of the above optional elements to 0.001-0.5wt%.
[0014] The copper alloy wire of the present invention has a tensile strength of more than 400 MPa and a conductivity of more than 65% IACS. The copper alloy wire is subjected to a 1% strain stress load and then unloaded cyclically until the copper alloy wire breaks, and the number of cycles of the copper alloy wire is more than 10,000 times.
[0015] The copper alloy wire of the present invention can be a round wire, a flat wire, etc., and a coating can be added on its surface. The copper alloy wire of the present invention with a coating is particularly suitable as a raw material for components of electronic and electrical equipment such as automotive wiring harnesses. The elements in the coating are not limited to the mass percentage composition range of the copper alloy wire of the present invention.
[0016] The second technical problem to be solved by the present invention is to provide a method for preparing a high-strength and high-conductivity copper alloy wire with excellent tensile fatigue performance in view of the deficiencies in the prior art.
[0017] The technical solution adopted by the present invention to solve the second technical problem is: a method for preparing a high-strength and high-conductivity copper alloy wire, the preparation process includes: melting, hot working, rough cold working, intermediate heat treatment and fine cold working, the intermediate heat treatment and the fine cold working are two processes as one cycle step, the cycle step is repeated for several rounds, and the pass processing rate of the fine cold working after the last intermediate heat treatment of the several cycles is 10-20%. The above-mentioned hot working can be performed by hot rolling, hot forging, extrusion and the like, and the rough cold working and fine cold working can be performed by cold rolling, stretching and the like.
[0018] The copper alloy wire of the present invention will undergo an intermediate heat treatment after rough cold working. The heat treatment eliminates the influence of lattice distortion and reduces the degree of work hardening, so that the subsequent fine cold working can be carried out smoothly. At the same time, the heat treatment above the recrystallization temperature causes the grains to rearrange, and the texture and organization also change accordingly. Controlling the processing rate of the fine cold working after the last intermediate heat treatment can more directly regulate the texture state of the final product, thereby improving the tensile fatigue performance of the wire. After repeated research and experiments, the inventors found that limiting the processing rate of the fine cold working after the last intermediate heat treatment can suppress <100> Crystalline oriented silk texture <110> and <111> Wire texture transformation, therefore, in the method for preparing the copper alloy wire of the present invention, the pass processing rate of the fine cold working after the last intermediate heat treatment is controlled at 10-20%.
[0019] Preferably, the last intermediate heat treatment is an online heat treatment, and its speed is controlled at 2-10 m / min. Copper alloy is a metal with underlying dislocation energy. During heat treatment, recrystallization is used to eliminate lattice distortion, reduce lattice defects such as vacancies, dislocation density, subgrain boundaries, and stacking faults. The grains are rearranged and the orientation is changed, which leads to changes in the properties of the copper alloy, such as reduced strength, improved electrical conductivity, and increased elongation. In the preparation process of the copper alloy wire of the present invention, the last intermediate heat treatment is performed online, and the speed of the online heat treatment is controlled, so that the degree of grain rearrangement can be more thorough, so that the texture state of the surface and center of the wire can be further regulated by subsequent fine cold processing; on the other hand, the appropriate speed of online heat treatment can effectively adjust the growth of the grains to obtain a good grain size, so that the wire strength is not insufficient due to the grain size being too small, and the tensile fatigue performance of the wire is not affected due to the grain size being too large.
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] (1) The present invention controls the texture of the Cu-Sn alloy wire, specifically, the microstructure of the cross section of the wire. <100> , <110> and <111> The area percentage of the wire texture is regulated to improve the tensile fatigue performance while taking into account the strength and conductivity of the wire.
[0022] (2) The copper alloy wire of the present invention can achieve a tensile strength of more than 400 MPa and a conductivity of more than 65% IACS; a stress load of 1% strain is cyclically applied to the copper alloy wire and then unloaded until the copper alloy wire breaks, and the number of cycles of the copper alloy wire is more than 10,000 times; while having high strength and high conductivity, it also has excellent tensile fatigue performance, and can be applied to automotive wiring harnesses, medical wiring harnesses, industrial robots, consumer electronics and other fields. DETAILED DESCRIPTION
[0023] The present invention is further described in detail below with reference to the embodiments.
[0024] The ingredients of Examples 1 to 10 and Comparative Examples 1 to 3 were used to prepare copper alloy round wires with a diameter of 0.1 mm. The preparation process was horizontal continuous casting → cold rolling → intermediate heat treatment → cold drawing → intermediate heat treatment → cold drawing → intermediate heat treatment → final cold drawing, which specifically included the following steps:
[0025] (1) The ingredients were prepared according to the compositions of the embodiments and comparative examples in Table 1, and smelted at 1100-1300° C. After the melt composition was tested to be qualified, horizontal continuous casting was performed to obtain a 20 mm billet;
[0026] (2) cold rolling the 20 mm Ø billet to obtain a 15 mm Ø billet;
[0027] (3) Perform intermediate heat treatment on the Ø15 mm billet at a temperature of 550°C and a holding time of 0.1 to 2 h;
[0028] (4) After cooling during intermediate heat treatment, cold drawing is performed to obtain a wire blank with a diameter of 6 mm;
[0029] (5) Perform intermediate heat treatment on the 6 mm diameter wire billet at a temperature of 500 ° C and a holding time of 0.1 to 2 h;
[0030] (6) After cooling during intermediate heat treatment, cold drawing is performed to obtain a wire blank with a diameter of 1.5 mm;
[0031] (7) The 1.5 mm diameter wire blank is subjected to a final intermediate heat treatment by online heat treatment, specifically, online heat treatment is adopted, the heat treatment temperature is 450° C., and the heat treatment rate is shown in Table 1;
[0032] (8) After cooling from the last intermediate heat treatment, the final cold drawing is performed. The specific parameters are shown in Table 1, and finally a wire sample with a diameter of 0.1 mm is obtained.
[0033] The difference between Comparative Example 1 and Examples 1 to 10 is that the composition of Comparative Example 1 is not within the composition range of the copper alloy wire of the present invention.
[0034] The alloy compositions of Comparative Examples 2 to 3 are the same as those of Example 2, except that the processing rates of the final cold drawing passes of Comparative Examples 2 to 3 are not within the control range of the present invention.
[0035] The wire samples obtained in Examples 1 to 10 and Comparative Examples 1 to 3 were evaluated for their characteristics under the following conditions.
[0036] Tensile strength: The room temperature tensile test is carried out in accordance with GB / T 228.1-2021 Metallic Materials Tensile Test Part 1: Room Temperature Test Method. The tensile strength of the wire sample is tested on an electronic universal mechanical properties testing machine.
[0037] Conductivity: The conductivity of the wire sample is tested using the "GB / T 32791-2016 Eddy Current Test Method for Electrical Conductivity of Copper and Copper Alloys".
[0038] Tensile fatigue performance: Take a sample of the same specification as the tensile strength test as the specimen, fix one side of the specimen, apply an axial stress load on the other side to perform a tensile test, then unload it to a strain-free state, cycle until the specimen breaks and fails, and record the number of cycles. The above load size is the corresponding load when causing 1% strain on the specimen.
[0039] Texture: EBSD method is used to observe the cross section of the sample along the axial direction. The surface with an angle of less than 10 degrees from the opposite orientation is defined as the corresponding orientation surface. <100> noodle, <110> Face to face <111> The percentage of the area of oriented grains to the total area is defined as <100> , <110> and <111> Area percentage of silk texture S 100 , S 110 and S 111 , calculate S 100 / (S 110 +S 111 ) value.
[0040] The central layer is defined as the area proportionally reduced from the center point of the wire cross section. The central layer accounts for 36% of the area on the wire cross section. The surface layer is defined as the area on the wire cross section except the central layer. The EBSD method is also used to test the surface layer. <110> The percentage of oriented grain area to total area S 表110 , the center layer <110> The percentage of oriented grain area to total area S 中110 , and calculate S 表110 / S 中110 The value of .
[0041] Grain size: The EBSD method is used to observe the cross section of the sample in a 10μm×10μm viewing area for testing. The boundaries with an orientation of more than 5° are regarded as grain boundaries. The length values of the long axis and short axis of each grain are observed and measured. The average value of the long axis length value and the short axis length value of the grain is defined as the average grain size. All average grain sizes in the viewing area are calculated and averaged.
[0042] The alloy compositions of Examples 1 to 10 and Comparative Examples 1 to 3 are shown in Table 1, and the properties are shown in Table 2.
[0043] By comparing the comprehensive properties of the alloy examples of the present invention with the comparative alloys, it is found that the copper alloy wire of the present invention exhibits excellent comprehensive properties such as tensile strength and electrical conductivity, and also has excellent tensile fatigue performance, with a tensile strength of more than 400 MPa and a conductivity of more than 65% IACS. The copper alloy wire of the present invention is subjected to a load of 1% strain and unloaded cyclically until the copper alloy wire breaks, and the number of cycles of the copper alloy wire is more than 10,000 times, indicating that the copper alloy wire of the present invention has high strength and high electrical conductivity as well as excellent tensile fatigue performance.
[0044] The Sn content of Comparative Example 1 is too high, which significantly affects the electrical conductivity and tensile fatigue properties of the wire; the processing rate of the final cold drawing pass of Comparative Example 2 is too low, the wire texture organization is not within the scope of the present invention, and the tensile fatigue performance is poor; the processing rate of the final cold drawing pass of Comparative Example 3 is too high, and breakage occurs; and the speed of the last intermediate heat treatment of Examples 6, 9 and 10 is not controlled within a further preferred range, resulting in coarsening of the grain size or changes in the texture state of the surface layer and the center layer, etc. Compared with other examples, they show relatively low tensile fatigue performance, but still meet the requirements.
[0045] Table 1 Composition and key process parameters of the alloys of the embodiment and comparative example
[0046]
[0047] Table 2 Properties of Example and Comparative Example Alloys
[0048]
Claims
1. A high-strength and high-conductivity copper alloy wire, characterized in that: The mass percentage composition of the copper alloy wire is Sn: 0.10~1.0%, the balance is Cu and inevitable impurities; in the microstructure of the cross section of the copper alloy wire, <100> , <110> and <111> Area percentage of silk texture S 100 , S 110 and S 111 Satisfaction: S 100 / (S 110 +S 111 )≥0.
8.
2. The high-strength and high-conductivity copper alloy wire according to claim 1, characterized in that: In the microstructure of the cross section of the copper alloy wire, the surface layer and the center layer <110> Area percentage of silk texture S 表110 and S 中110 Satisfaction: S 表110 / S 中110 ≥1.2, the central layer is a region that is proportionally reduced with the central point of the cross section of the copper alloy wire as the center, and the area of the central layer on the cross section of the copper alloy wire accounts for 36%, and the surface layer is the region on the cross section of the copper alloy wire excluding the central layer.
3. The high-strength and high-conductivity copper alloy wire according to claim 1, characterized in that: The average grain size in the microstructure of the cross section of the copper alloy wire is 0.5 to 10 μm.
4. The high-strength and high-conductivity copper alloy wire according to claim 1, characterized in that: The copper alloy wire also includes at least one element selected from Zn, Mg, Al, Ni, Mn, Si, Ti, Cr, Ag, Zr, In, P and B in a total amount of 0.001-0.5%.
5. The high-strength and high-conductivity copper alloy wire according to any one of claims 1 to 4, characterized in that: The copper alloy wire has a tensile strength of more than 400 MPa and a conductivity of more than 65% IACS.
6. The high-strength and high-conductivity copper alloy wire according to any one of claims 1 to 4, characterized in that: A stress load of 1% strain was cyclically applied to the copper alloy wire and then unloaded until the copper alloy wire broke, and the number of cycles of the copper alloy wire was more than 10,000 times.
7. The high-strength and high-conductivity copper alloy wire according to any one of claims 1 to 4, characterized in that: A plating layer is added on the surface of the copper alloy wire.
8. The method for preparing a high-strength and high-conductivity copper alloy wire according to any one of claims 1 to 7, characterized in that: The preparation process includes: melting, hot working, rough cold working, intermediate heat treatment and fine cold working. The intermediate heat treatment and the fine cold working are one cycle step, and the cycle step is repeated for several rounds. The processing rate of the fine cold working after the last intermediate heat treatment of the several cycles is 10-20%.
9. The method for preparing a high-strength and high-conductivity copper alloy wire according to claim 8, characterized in that: The last intermediate heat treatment is an online heat treatment, and the speed is controlled at 2-10 m / min.